New species of Rhopalomyia and Dasineura (Diptera: Cecidomyiidae) associated with Prosopis caldenia Burkart (Fabaceae) in Argentina - Cornejo, Laura Gabriela; Molas, Bárbara Mariana Corró; Kuzmanich, Nicolás; Martínez, Juan José (Zootaxa, 2019)
Two new species of cecidomyiids were identified on Prosopis caldenia Burkart (Fabaceae) in Argentina: Rhopalomyia caldeniae Cornejo & Martínez sp. nov., as the inducer of bivalve leaf galls, and the inquiline Dasineura oportunista Cornejo & Martínez sp. nov. These galls are composed of the partial coalescence of two contiguous pinnulae that delimit a single larval chamber, where both species develop. Seven other species were reared from these galls as parasitoids and inquilines.